Examining the Role of Principals in Monitoring Instructional Practices in the Literacy Classroom - Bernadictus O. Plaatjies (Social Sciences and Education Research Review)
Literacy is essential for children's academic success. School principals as instructional leaders are responsible for ensuring the comprehensive and effective implementation of the instructional program. This qualitative study explored the role of principals in monitoring literacy instruction practices through a scoping review of the literature, using the Instructional leadership theory as a theoretical lens. The findings revealed that monitoring literacy instruction has failed for several reasons, including principals' lack of subject knowledge. Furthermore, the findings showed the need for better monitoring in literacy instruction according to a distributed approach. Since the study showed serious shortcomings in monitoring practices, further empirical research on this topic is imperative.